Oligonucleotide-Palladacycle Conjugates as Splice-Correcting Agents - Hande M; Saher O; Lundin KE; Smith CIE; Zain R; Lonnberg T (MDPI, 2025)
2'-O-Methylribo phosphorothioate oligonucleotides incorporating cyclopalladated benzylamine conjugate groups at their 5'-termini have been prepared and their ability to hybridize with a designated target sequence was assessed by conventional UV melting experiments. The oligonucleotides were further examined in splice-switching experiments in human cervical cancer (HeLa Luc/705), human liver (HuH7_705), and human osteosarcoma (U-2 OS_705) reporter cell lines. Melting temperatures of duplexes formed by the modified oligonucleotides were approximately 5 degrees C lower than melting temperatures of the respective unmodified duplexes. The cyclopalladated oligonucleotides functioned as splice-correcting agents in the HeLa Luc/705 cell line somewhat more efficiently than their unmodified counterparts. Furthermore, the introduction of this chemical modification did not induce toxicity in cells. These results demonstrate the feasibility of using covalently metalated oligonucleotides as therapeutic agents.